PENGARUH TRANSPARANSI, AKUNTABILITAS DAN PARTISIPASI TERHADAP GOOD GOVERNANCE PADA ZIS KECAMATAN CICURUG KABUPATEN SUKABUMI - Aulia, L.S.; Setiawan, A.B.; Melani, M.M. (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of transparency, accountability and participation on good governance at the ZIS institution in Cicurug District, Sukabumi Regency. The population in this study were all ZIS administrators in Cicurug District and people in Cicurug District who were hypocrites. The sample in this study was 66 people with purposive sampling technique. The research instrument used a questionnaire with a Likert scale. Testing data analysis using multiple linear regression analysis. The results showed that simultaneously transparency, accountability and participation had a positive and significant effect on good governance at ZIS, Cicurug District, Sukabumi Regency. Partially, all independent variables have a positive and significant effect on good governance in ZIS, Cicurug District, Sukabumi Regency. The magnitude of the contribution of the influence of transparency, accountability and participation on good governance of ZIS is 81.3%.